Pemberdayaan Keterampilan Guru Melalui Pembelajaran Problem Based Learning Dalam Meningkatkan Karakter Siswa di Sekolah Dasar - Alberth Manurung; Abdul Halim; Ainur Rosyid (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Problem Based Learning (PBL) is a problem-based learning model that uses intelligence so that it is able to deal with anything new and complex. Problem Based Learning is a model that aims to instill and develop the learning process in teachers. The purpose of this community service activity is to empower teacher skills through Problem Based Learning is to increase knowledge which changes every time. The subject of this community service is all teachers at SDN Kenari 07 Pagi. Based on the results of observations at Kenari 07 Pagi Elementary School, the teacher's learning process still uses conventional or teacher-centered teaching as a provider of information, with the empowerment of teacher skills it is hoped that it will improve the good character of students from each concept of working on problems in the form of application questions. Based on this, recommendations for solutions to problems need to be carried out through mentoring activities and empowering teacher skills through Problem Based Learning in Improving Student Character Education. Mastery of Teacher skills through Problem Based Learning both when learning is done at school or studying at home (online). The methods used are socialization, self-reflection and program mapping, measurement and evaluation